Effects of the replacement of fishmeal with defatted black soldier fly (Hermetia illucens) larvae meal in high lipid diets on growth, serum liver antioxidant and disease resistance in the hybrid grouper (Epinephelus fuscoguttatus ♀ × E. lanceolatus ♂) - Weibin Huang; Wanting Huang; Wenshan Cai; Hao Liu; Menglong Zhou; Beiping Tan; Hengyang Song; Xiaohui Dong (Aquaculture Reports)
A previous study showed that high lipid (16 %) diet could reduce protein content from 50 % to 45 % without affecting growth performance of hybrid grouper (Epinephelus fuscoguttatus ♀ × E. lanceolatus ♂). In this experiment, defatted black soldier fly (Hermetia illucens) larvae meal was added to the formula to replace fish meal (FM), in part to address the current shortage and high price of FM. The effects on growth performance, serum and liver antioxidant and immune function, liver morphology and disease resistance of grouper were investigated by replacing 0 (FM content in the control: 40 %), 20, 40, 60 and 80 % FM with defatted black soldier fly larvae meal. A total of 450 fish were included in the experiment and randomly assigned to 15 fiber tanks (1 m3) for eight weeks. The result shows that dietary FM content can be reduced to 32 % with the defatted black solider fly larvae meal as an alternative, when substitution levels continued to rise, growth performance was significantly reduced (P < 0.05). In serum, the content of IgM in DSM20 group was significantly higher than FM group (P < 0.05). T-AOC was significantly higher in DSM20 and DSM40 groups than in other groups (P < 0.05). And there was no significant difference in SOD. In liver, DSM40 group had the highest T-AOC content, which was higher than other group (P < 0.05). Compared to other groups, the FM group's IgM content was considerably reduced (P < 0.05). In addition, high levels of fish meal substitution can damage liver morphology, as well as regulate the expression levels of liver antioxidant and immune genes. In general, defatted black soldier fly larvae meal can reduce FM to 32 % without affecting its growth. Proper defatted black soldier fly larvae meal can improve the antioxidant and immunity of serum and liver.